Pengaruh Tiktok Self-control Failure Terhadap Prokrastinasi Akademik Mahasiswa Tadris Matematika - Azza Nur Lailah; Farha Ashiilah Herwinsyah; Rif'at Qonitatullah; Ulfia Churidatul Andriani (Program Studi Tadris Matematika Fakultas Tarbiyah Institut Agama Islam Al-Qolam Malang, 2025)
This study aims to examine the effect of TikTok self-control failure on academic procrastination among Mathematics Education students at Maulana Malik Ibrahim State Islamic University Malang. The research sample consisted of 59 students from the 2022 cohort. Data were collected through questionnaires measuring TikTok self-control failure and academic procrastination, then analyzed using simple linear regression assisted by SPSS version 27. The results revealed a significant influence of self-control failure in TikTok usage on students’ academic procrastination behavior. The regression coefficient of 0.198 with a significance value of 0.010 indicates that the higher the level of self-control failure while using TikTok, the greater the tendency for students to delay their academic tasks. These findings emphasize the importance of managing social media use and strengthening self-control skills to minimize procrastination behavior, which negatively impacts students’ academic achievement. This study contributes to understanding the influence of social media on academic behavior in the digital era.